2004
DOI: 10.1097/01.ccm.0000120057.04528.60
|View full text |Cite
|
Sign up to set email alerts
|

Osmole gap in neurologic-neurosurgical intensive care unit: Its normal value, calculation, and relationship with mannitol serum concentrations

Abstract: The osmole gap correlates better with mannitol serum concentrations than osmolality, and although it cannot predict a specific mannitol serum concentration, a normal osmole gap concentration, as we find at trough times, indicates sufficient clearance for a new mannitol dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 27 publications
0
46
0
2
Order By: Relevance
“…As mannitol is often initiated under emergent conditions, baseline osmolality was not measured in a significant proportion of patients before administration of the first dose. Furthermore, we have shown that serum sodium, when measured immediately prior to a mannitol dose, correlates closely with serum osmolality (19), making the change in sodium an accurate surrogate of the osmotic response to mannitol.…”
Section: Groupsmentioning
confidence: 98%
“…As mannitol is often initiated under emergent conditions, baseline osmolality was not measured in a significant proportion of patients before administration of the first dose. Furthermore, we have shown that serum sodium, when measured immediately prior to a mannitol dose, correlates closely with serum osmolality (19), making the change in sodium an accurate surrogate of the osmotic response to mannitol.…”
Section: Groupsmentioning
confidence: 98%
“…Por outro lado, pacientes comatosos com sinais de hipertensão intracraniana podem se beneficiar de medidas, como elevação da cabeceira a 30 graus, analgesia, sedação, doses moderadas de manitol a 20%, solução salina hipertônica e hiperventilação para atingir PaCO 2 entre 28 e 32 mmHg. Entretanto, não há evidências definitivas sobre o benefício do uso destas terapias para pacientes com HIC até o momento [81][82][83][84] . Um estudo que avaliou o uso de corticosteróides (dexametasona) em pacientes com HIC não mostrou benefícios e revelou um aumento no risco de infecções 85 .…”
Section: Hipertensão Intracranianaunclassified
“…Monitoring serum osmolarity in these patients does not appear to predict the development or risk of acute renal failure [calculated osmolality formula: 2(Na) + glucose/18 + blood urea nitrogen/2.8] [58,59]. Withholding mannitol should also be considered if the serum osmolality exceeds 320 mOsm/L, although little evidence exists to support this number as the upper limit.…”
Section: Hyperosmolar Therapymentioning
confidence: 99%